APPLICATION OF GASTROENTEROLOGICAL QUESTIONNAIRE GSRS IN DIAGNOSTICS OF GASTROINTESTINAL DYSFUNCTION IN LATE ELDERLY PATIENTS WITH ARTHROSIS ON THE DIABETES BACKGROUND - S.I. KIRILINA; V.S. SIROTA; G.G. SIROTA; V.A. AYRUMYAN (Avicenna Tajik State Medical University, 2019)
Objective: To evaluate the results of the GSRS gastroenterological questionnaire as an express test in identifying gastrointestinal dysfunction in patients over 75 years old who have been taking non-steroidal anti-inflammatory drugs (NSAIDs) with coxarthrosis and gonarthrosis in the presence of type 2 diabetes mellitus (T2DM). Methods: Assessment of the severity of gastroenterological complaints carried out with the help of the GSRS questionnaire of quality of life in 100 patients over 75 with coxarthrosis and gonarthrosis. Group I included 60 patients with a concomitant of T2DM; group II included 40 patients without diabetes. Results: The statement and analysis of general clinical data in groups allowed to calculate the frequency of clinical manifestations of gastroenterological syndromes and their average numerical score on the GSRS questionnaire. The average total survey score was significantly higher in the group of patients with coxarthrosis and gonarthrosis on the background of T2DM. Constipation, reflux, and dyspeptic syndromes were not identical in both groups and had statistically significant differences. Confirmed more pronounced violations of motor-evacuation function (MEF) of the gastrointestinal tract in a group of patients with coxarthrosis and gonarthrosis on the background of T2DM. Conclusion: In order to prevent hypo- or hyperglycemic states in the perioperative period in patients with coxarthrosis and gonarthrosis, it is advisable to use the GSRS gastroenterological quality of life questionnaire, which allows identifying oppression of the MEF of the gastrointestinal tract. Patients with coxarthrosis and gonarthrosis and concomitant of T2DM who take long term receiving NSAIDs have a more pronounced dysfunction of the gastrointestinal tract.